2014
DOI: 10.2151/jmsj.2014-a12
|View full text |Cite
|
Sign up to set email alerts
|

Use of 315 nm Channel Data of the Sky Radiometer to Estimate the Columnar Ozone Concentration: A Preliminary Study

Abstract: The sky radiometer is a ground-based instrument implemented to investigate the characteristics of not only aerosols but also clouds and water vapor. This study is the first attempt to bring this instrument in use to estimate the columnar ozone concentration (U). A method and preliminary results related to the estimation of U using the 315-nm-channel data of the sky radiometer are presented. The proposed method consists of calculating the calibration constant for direct intensity at 315 nm wavelength, F 0 (315 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…The POM-02 data were processed by Skyrad pack 4.2. They found an RMSD of 0.025 at 440 nm and 0.018 at other wavelengths, which is similar to the findings of Khatri et al(2016), even with the mean AOT at this site being as large as 0.33 at 675 nm. RMSDs of the Ångström exponent were 0.19 between 440 and 870 nm and 0.28 between 500 and 870 nm, though this is not shown in Table 5.…”
Section: Retrievals Of Parameters For Atmospheric Constituentssupporting
confidence: 80%
See 1 more Smart Citation
“…The POM-02 data were processed by Skyrad pack 4.2. They found an RMSD of 0.025 at 440 nm and 0.018 at other wavelengths, which is similar to the findings of Khatri et al(2016), even with the mean AOT at this site being as large as 0.33 at 675 nm. RMSDs of the Ångström exponent were 0.19 between 440 and 870 nm and 0.28 between 500 and 870 nm, though this is not shown in Table 5.…”
Section: Retrievals Of Parameters For Atmospheric Constituentssupporting
confidence: 80%
“…Figure 8a and Table 5 compare observed AOT values with those of AERONET at four co-located sites of Chiba (Japan), Pune (India), Valencia (Spain), and Seoul (South Korea) (Khatri et al, 2016). They found that RMSDs were 0.019 at 675 nm and about 0.015 at 870 and 1020 nm with a site dependence of 0.010, 0.033, 0.009, and 0.022 at 870 nm at the four sites, respectively, though this is not shown in Table 5.…”
Section: Retrievals Of Parameters For Atmospheric Constituentsmentioning
confidence: 99%
“…Spectral V 0 values of two consecutive calibration dates are linearly interpolated to analyze observation data of intermediate dates. This strategy is based on the assumption of the linear change of V 0 with time, which may not always valid in the real atmosphere as shown by Khatri et al []. The uncertainty in AOT for AERONET field instruments, primarily due to V 0 uncertainty, is reported to be ~0.01 to 0.021 at different wavelengths with higher errors in the ultraviolet channels [ Eck et al , ].…”
Section: Major Differences Between Aeronet and Skynet Strategiesmentioning
confidence: 99%
“…The columnar ozone amount is retrieved from the direct solar irradiance measurement of 315 nm channel for the Huggins band. Khatri et al (2014) determined the F 0 -value by a ML method Eq. (22) assuming b g =1 for ozone without a significant line absorption structure.…”
Section: Retrievals Of Parameters For Atmospheric Constituentsmentioning
confidence: 99%